Answer:
It should be greater i would think
Y - y1 = m(x - x1)
y + 7 = (-1/8)(x - 9)
y + 7 = (-1/8)x + 1.125
Subtract 7 from both sides
y = -1/8x - 5.875
Answer:
An equation which has the same solution as the given equation is:
( x - 18 ) ( x + 2 ) + 48 = 0 ....
Step-by-step explanation:
The given expression is:
x2-16x+12
Break the constant term:
x^2-16x-36 +48=0
[x^2-16x-36] +48=0
Now break the middle term inside the brackets
(x^2-18x+2x-36)+48=0
Take the common
[x(x-18) +2(x-18)]+48=0
(x-18)(x+2)+48=0
Thus an equation which has the same solution as the given equation is:
( x - 18 ) ( x + 2 ) + 48 = 0 ....
Top left -4,4
Top right 4,4
Bottom left -2,-2
Bottom right 4,0